Self-management interventions for chronic pain. (May 2013) - Mann, Elizabeth G; LeFort, Sandra; VanDenKerkhof, Elizabeth G
SUMMARY  Individuals living with chronic pain face daily challenges of managing symptoms, modifying roles and responsibilities, and coping with the negative emotional consequences of pain. Self-management interventions teach a variety of strategies to meet these challenges and build participants' self-efficacy for their use. These interventions have been delivered in individual, group and online formats for a variety of different pain conditions. The evidence supports the efficacy of self-management interventions in improving pain, mental health and health-related quality of life outcomes. Acceptance of the chronic nature of their pain is a necessary step before individuals are ready to self-manage. Clinicians can play a critical role in supporting self-management through answering questions, providing advice, addressing barriers and facilitators, and encouraging self-management efforts.